Исследование температуры массива горных пород Березовского рудника ОАО «Беларуськалий» - Зайцев А. В. Артем Вячеславович; Бородавкин Д. А. Дмитрий Алексеевич; Бублик С. А. Сергей Анатольевич; Агеева К. М. Ксения Михайловна (2022, 2022)
Заглавие с титульного листа